In-Silico Analysis of Agrocybe aegerita Bioactive Compounds Targeting HER-2 Positive Breast Cancer Protein - Moses, Iyekekpolor Osamudiame (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This study explores the anti-cancer potential of bioactive compounds derived from Agrocybe aegerita, focusing on their interaction with the HER-2 protein, which is commonly overexpressed in aggressive breast cancers. Using in-silico molecular docking techniques via the SwissDock platform and AutoDock Vina algorithm, the binding affinities of three bioactive compounds—ceramide, ganoderic acid, and galectin—were evaluated and compared to standard cancer drugs, including doxorubicin, lapatinib, and pazopanib. The results demonstrated that ganoderic acid exhibited the highest binding affinity to HER-2 (-6.34 to -6.18), comparable to lapatinib and pazopanib, suggesting its strong therapeutic potential. Ceramide and galectin showed moderate affinities, indicating possible roles in complementary or synergistic therapies. The findings suggest that A. aegerita, particularly its ganoderic acid compound, holds promise as a natural source for novel anti-cancer agents, potentially offering comparable efficacy to synthetic drugs with fewer side effects. However, the limitations of in-silico studies are acknowledged, and further in vitro and in vivo validation is necessary to confirm these promising results. This research contributes to the growing body of knowledge on natural bioactive compounds, underscoring the potential of mushrooms in cancer therapy and advocating for more extensive studies to harness their medicinal properties.